PENGARUH PROFITABILITAS (ROA), LIKUIDITAS (CR), DAN STRUKTUR AKTIVA (SA) TERHADAP STRUKTUR MODAL PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DI BEI TAHUN 2020-2024 - Leliana, Silvia; Hasanudin, Hasanudin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of profitability, liquidity, and asset structure on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period, both partially and simultaneously. This study uses a descriptive quantitative method with a statistical analysis approach. The population in this study is the financial statements of food and beverage companies listed on the Indonesia Stock Exchange, while the sample consists of data taken from the companies' financial statements from 2020 to 2024. The independent variabels in this study consist of profitability (Return on Assets), Liquidity (Current Ratio), and Asset Structure, while the dependent variabel is Capital Structure (Debt to Equity Ratio). The results of this study indicate that partially, profitability has a significant effect on capital structure. Meanwhile, Liquidity and Asset Structure do not significantly influence the company's capital structure. Simultaneously, all three independent variabels significantly influence the company's capital structure.